Bullying and Cyberbullying during the COVID-19 Pandemic: A survey of the school population. - ZANETTI, Maria Assunta; MARINONI, Carlo; PEDRONI, Sofia (RiCOGNIZIONI. Rivista di Lingue e Letterature straniere e Culture moderne, 2022)
In the aftermath of the COVID 19 pandemic, social relationships were severely compromised and the lockdown forced people to stay at home, forcing them to interface, exclusively, via social-networks. The research group of the University of Pavia wanted to investigate whether this overexposure to social networks has had a negative influence on the phenomenon of cyberbullying; in addition to this, they wanted to investigate what perception young people had of the lockdown and how they experienced the impossibility of hanging out, offline, with their peers.